Relations among intrinsic and extrinsic reading motivation, reading amount, and comprehension: a conceptual replication - Troyer, Margaret; Kim, James S.; Hale, Elizabeth; Wantchekon, Kristia A.; Armstrong, Catherine (Reading & writing, 2019)
Children’s motivation to read is a strong predictor of their reading comprehension. However, some recent research has suggested that the relationship between reading motivation and reading comprehension may be mediated through the amount that students read. This study attempts a conceptual replication of several existing models that explore the relationship among children’s reading motivations, out-of-school reading amount, and reading comprehension, using a large sample of over 4000 third- through fifth-graders in 59 U.S. elementary schools. Consistent with prior research, several control variables, including children’s prior reading comprehension ability, gender, and socioeconomic status, directly contributed to later reading comprehension. Results also replicated positive associations between intrinsic reading motivation, reading amount and reading comprehension, and negative associations between extrinsic reading motivation, reading amount and reading comprehension. Using structural equation models, our analyses found no evidence that the relationship between children’s intrinsic and extrinsic reading motivation and later reading comprehension was either partially or fully mediated by reading amount. This suggests that it is critical to attend to context-specific determinants of motivation and reading amount, including students’ background characteristics and quality of texts read. Furthermore, this study underscores the importance of replicating methods used by original researchers to confirm and disconfirm hypotheses, and of conducting research with large and diverse samples that enhance the generalizability of results.